The Utilization of Burungnesia to Detect Citizen Scientist Participation Preference in Birding Sites Observation in Java Island - Winnasis, Swiss; Hakim, Luchman; Imron, M. Ali (Journal of Indonesian Tourism and Development Studies, 2018)
The contribution of citizen scientist in conservation field has been recognized important, but it is few studied in Indonesia. Citizen Science especially important in bird conservation. The aims of the research is to assess the citizen scientist preference in site selection and its relationship to the success to complete observer's checklist in Java Island. This study confirmed that citizen sciences is effective in collecting field data of birds. It is especially useful to record common birds, birds with high population number, and general birds. Special birds and birds in small population seems to be rarely reported by citizen scientist. Lowest preferred location often has limitation of accessibility. Citizen scientist has more preference to select sites for bird observation in wild habitat. Keywords: Birds conservation, conservation, public participation, Burungnesia.